The role of the adhesion molecule Nectin-4 in the pathogenesis of endometriosis - BAĞCI ÇULÇİ, PELİN (I R O G CANADA, INC, 2016)
Objective: Nectins are immunoglobulin-like adhesion molecules, and they play important role in cell proliferation and tumor metastasis. The objective in this study was to compare the expression of Nectin-4 in normal endometrium and in ectopic endometriotic tissues. Materials and Methods: Nectin-4 expression was investigated in ovarian endometriosis (n=20), peritoneal endometriosis (n=20), endometrium of endometriosis (n=20), and in a control group (having no endometriosis) (n=20) by immunohistochemical method. Results: Nectin-4 expression, when compared with control group, was higher in endometriotic lesions of patients having ovarian endometriosis and peritoneal endometriosis (p = 0.003 andp = 0.009, respectively). This difference was significant in the endometrium of patients having endometriosis (p = 0.011). Conclusion: The authors believe that Nectin-4 molecule may contribute to the pathogenesis of endometriosis. For this reason, the use of medicines developed against this molecule in the treatment of endometriosis may be useful.
Keywords: Endometriosis; Nectin-4; Immunohistochemistry; EUTOPIC ENDOMETRIUM; DIFFERENT PROFILE; TISSUES EXPRESS; OVARIAN; CANCER; PERITONEAL